СОВРЕМЕННОЕ СОСТОЯНИЕ БИОРАЗНООБРАЗИЯ ЮЖНОГО ПРИАРАЛЬЯ - Кудайбергенова, У.К. (SCIENCE and SOCIETY, 2024)
In the article the questions of the modern state of biodiversity of Southern Priaralie and perspective directions of development of ecological tourism in this region. There is the intensive mastering of territory of plateau Usturt, that is accompanied by influence of anthropogenic factors on the dynamics of landscape, vegetable associations and specific variety of fauna. In this connection the permanent monitoring of biodiversity, and also investments is needed in development of tourist infrastructure.
Keywords: southern Priaralie; plateau Usturt; monitoring; biodiversity; eco-tourism